The famous five : five on kirrin Island again - Blyton, Enid. (b, 2015)
Uncle Quentin is busy working on Kirrin island -- and it's all top secret! He doesn't want anyone to visit, not even the Famous Five. But the island is full of hiding places and Uncle Quentin is not alone. Someone wants to steal his ideas and ruin his plans. George is determined to find her father and save her island, no matter what dangers await. She can't do it without the others--can they help her in time?
Keywords: Action and adventure fiction